Evidence of a role for foliar salicylic acid in regulating the rate of post-ingestive protein breakdown in ruminants and contributing to landscape pollution - Kingston-Smith, Alison H (Journal of experimental botany, 2012)
Ruminant farming is important to global food security, but excessive proteolysis in the rumen causes inefficient use of nitrogenous plant constituents and environmental pollution. While both plant and microbial proteases contribute to ruminal proteolysis, little is known about post-ingestion regulation of plant proteases except that activity in the first few hours after ingestion of fresh forage can result in significant degradation of foliar protein. As the signal salicylic acid (SA) influences cell death during both biotic and abiotic stresses, Arabidopsis wild-type and mutants were used to test the effect of SA on proteolysis induced by rumen conditions (39 °C and anaerobic in a neutral pH). In leaves of Col-0, SA accumulation was induced by exposure to a rumen microbial inoculum. Use of Arabidopsis mutants with altered endogenous SA concentrations revealed a clear correlation with the rate of stress-induced proteolysis; rapid proteolysis occurred in leaves of SA-accumulating mutants cpr5-1 and dnd1-1 whereas there was little or no proteolysis in sid2-1 which is unable to synthesize SA. Reduced proteolysis in npr1-1 (Non-expressor of Pathogenesis Related genes) demonstrated a dependence on SA signalling. Slowed proteolysis in sid2-1 and npr1-1 was associated with the absence of a 34.6 kDa cysteine protease. These data suggest that proteolysis in leaves ingested by ruminants is modulated by SA. It is therefore suggested that influencing SA effects in planta could enable the development of forage crops with lower environmental impact and increased production potential